An Overview of the Digital Literacy Level of Healthcare Workers at Talaga Regional General Hospital, Majalengka, in 2026 - Syifa Choerunnisa; Maula Ismail Mohammad; Lina Khasanah; Bambang Karmanto (CV. Inara, 2026)
The rapid advancement of digital health technologies in the era of Industry 4.0 and Society 5.0 has necessitated adequate digital literacy among healthcare professionals; However, empirical evidence in regional hospitals remains limited. This study aims to describe the level of digital literacy among healthcare workers at a regional public hospital in 2026 based on eight dimensions of digital competence. A quantitative descriptive cross-sectional design was employed, involving all 90 healthcare workers through total sampling. Data were collected using a validated and highly reliable 21-item questionnaire (Cronbach's Alpha = 0.970) measured on a six-point Likert scale and analyzed using descriptive statistics. The findings indicated that overall digital literacy was at a high level (82%), with the highest score in the ability to find and select information (87%) and the lowest in functional skills (78%). All dimensions, including communication, collaboration, creativity, critical thinking, cultural understanding, and digital safety, were consistently categorized as high. These results suggest that healthcare workers demonstrate strong readiness to support digital health transformation, although technical skill enhancement remains necessary. The study contributes empirical evidence for developing targeted training programs and strengthening digital health implementation in regional healthcare settings.